Public Relations Management in Africa Volume 1
XXVI, 264 p. 8 illus.
Keywords: This two-part volume examines current pedagogical modules, research directions and other emerging issues in public relations and communication management in Africa. In comparison to its Western and Asian counterparts, the literature on public relations management in Africa is limited, and much of it is examined through the lenses of Western philosophies and pedagogies that do not generally resonate with Africa's socioeconomic, political, and cultural contexts. This book aims to change that. Through analyzing the organizational dynamic, Volume 1 brings together contributors from across Africa to provide valuable insights into how public relations contributes to organizational effectiveness on the continent. Chapters discussed include a review of public relations research in Africa, the role of the African CEO as a public relations activist, the use of social and digital media in public relations, the measurement and evaluation of communication programs, and the implications ofthe fourth industrial revolution on public relations practice in Africa. Providing important pathways and overviews of public relations management in Africa, this volume not only highlights current practices but offers insights into the future of the practice within its evolving global landscape. Albert A. Anani-Bossman (PhD) is a lecturer and Ag. Head of the Department of public relations in the Faculty of Public Relations, Advertising & Marketing, Ghana Institute of Journalism. Takalani E. Mudzanani is a professor of communication science at the University of South Africa (UNISA). Cornelius B. Pratt is Professor Emeritus of Global Communication and Leadership in the Lew Klein College of Media and Communication at Temple University in Philadelphia, United States. Isaac A. Blankson is a professor of communication and public relations and the president of the African University College of Communications (AUCC). .